2018
DOI: 10.1016/j.bbi.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal administration of antisense oligonucleotide against p38α but not p38β MAP kinase isoform reduces neuropathic and postoperative pain and TLR4-induced pain in male mice

Abstract: p38 mitogen-activated protein kinase (MAPK) consists of two major isoforms: p38α and p38β; however, it remains unclear which isoform is more important for chronic pain development. Recently, we developed potent, long-lasting, and p38 MAPK subtype-specific antisense oligonucleotides (ASOs). We examined the therapeutic effects of isoform-specific ASOs in several chronic pain models following single intrathecal injection (300 µg/10 µl) in CD1 mice. In the chronic constriction injury (CCI) model, p38α MAPK ASO, gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 61 publications
2
52
0
Order By: Relevance
“…Neuropathic pain models that are associated with persistent LPA signaling and subsequent activation of MAPK cascades might be candidates for such an approach [42]. Indeed, a series of recent reports demonstrated that pharmacological intervention strategies that attenuate MAPK signaling pathways (either directly or indirectly) alleviate hyperalgesia in preclinical animal models of neuropathic pain [58][59][60][61]. In one of our earlier proteome studies, we have shown that LPA affects the abundance of a number of metabolic enzymes involved in glycolysis [20].…”
Section: Discussionmentioning
confidence: 97%
“…Neuropathic pain models that are associated with persistent LPA signaling and subsequent activation of MAPK cascades might be candidates for such an approach [42]. Indeed, a series of recent reports demonstrated that pharmacological intervention strategies that attenuate MAPK signaling pathways (either directly or indirectly) alleviate hyperalgesia in preclinical animal models of neuropathic pain [58][59][60][61]. In one of our earlier proteome studies, we have shown that LPA affects the abundance of a number of metabolic enzymes involved in glycolysis [20].…”
Section: Discussionmentioning
confidence: 97%
“…In a separate study, a male-specific increase in phosphorylated p38-MAPK was also observed in microglia, and inhibition of p38-MAPK via intrathecal drug administration reduced PNI-and formalin-induced pain in male, but not female, rodents (Taves et al, 2016). It was later demonstrated that the key isoform driving pain in a sexdependent manner is p38 (Luo et al, 2018). Together, these data suggest that male microglia are uniquely prepared to mediate pain-inducing signaling.…”
Section: What Do We Know About Sex Differences In Spinal Microglia Anmentioning
confidence: 88%
“…Notably, microglia drive neuropathic pain and inflammatory pain in male animals (Rosen et al, 2017). Several microglial signaling molecules, including Toll-like receptor 4 (TLR4), p38 mitogen-activated protein kinase (MAPK), ATP receptor P2X4, and BDNF, exhibit sexually dimorphic functions in inflammatory and neuropathic pain (Sorge et al, 2011(Sorge et al, , 2015Taves et al, 2016;Luo et al, 2018;Mapplebeck et al, 2018;Inyang et al, 2019). Upstream activators of microglia, such as caspase-6, also display male-specific activity in the contexts of inflammatory and neuropathic pain (Berta et al, 2016;Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%